Epidermal Growth Factor Methods and Protocols - Patel, Tarun B.; Bertics, Paul J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2006)
Epidermal growth factor (EGF) and related molecules regulate a wide array of biological events, ranging from normal growth and development to such pathological states as cancer and cardiovascular diseases. In Epidermal Growth Factor: Methods and Protocols, expert researchers active in the field present their best methods to dissect the mechanisms that control growth factors and their regulators in both normal and pathological states. These readily reproducible techniques range from the study of purified EGF receptor to complex signaling and processing networks in intact cells, including a chapter on the clinical and pharmacological considerations of their use in cancer therapy. The protocols follow the successful Methods in Molecular Biology™ series format, each offering step-by-step laboratory instructions, an introduction outlining the principles behind the technique, lists of the necessary equipment and reagents, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and highly practical, Epidermal Growth Factor: Methods and Protocols offers investigators an array of powerful and proven tools to unravel the workings of epidermal growth factor, as well as develop new strategies for the successful use of this important developmental and therapeutic target.
A Historical Perspective of the EGF Receptor and Related Systems -- Purification and Assay of Kinase-Active EGF Receptor From Mammalian Cells by Immunoaffinity Chromatography -- Soluble Epidermal Growth Factor Receptor Acridinium-Linked Immunosorbent Assay -- Analysis of EGF Receptor Interactions With the ? Subunit of the Stimulatory GTP Binding Protein of Adenylyl Cyclase, Gs -- Regulator of Epidermal Growth Factor Signaling -- Dissecting the Epidermal Growth Factor Receptor Signal Transactivation Pathway -- A Sensitive Method to Monitor Ectodomain Shedding of Ligands of the Epidermal Growth Factor Receptor -- In Vitro and In Vivo Assays of Monoubiquitination of Receptor Tyrosine Kinases -- Assays to Monitor Degradation of the EGF Receptor -- Assessment of Degradation and Ubiquitination of CXCR4, a GPCR Regulated by EGFR Family Members -- Epithelial Cell Migration in Response to Epidermal Growth Factor -- Motility Signaled From the EGF Receptor and Related Systems -- Methods for Determining the Proliferation of Cells in Response to EGFR Ligands -- Clinical Advancement of EGFR Inhibitors in Cancer Therapy.
Keywords: Biochemistry; Cell biology; Biochemistry, general; Cell Biology